Proceedings TIE 2022 2022
DOI: 10.46793/tie22.431r
|View full text |Cite
|
Sign up to set email alerts
|

Digital Resilience and Psychological Wellbeing of Italian Higher Education Students: An Exploratory Study

Abstract: Covid-19 pandemic has increased the use of technology in the educational field. While previous literature has demonstrated the benefits of using technology in educational environments, the risks related to problematic digital behaviors have been less investigated. Digital resilience represents a protective factor for students’ learning outcomes and emotional wellbeing. The main aim of this study was to explore Italian university students’ digital resilience levels and their psychological wellbeing in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These results are similar to those of Ragni et al (16), which indicated that Italian higher education students had a high level of digital resilience. These data are in line with previous studies from other countries.…”
Section: General Descriptions Of Digital Resilience Of Adolescentssupporting
confidence: 91%
See 4 more Smart Citations
“…These results are similar to those of Ragni et al (16), which indicated that Italian higher education students had a high level of digital resilience. These data are in line with previous studies from other countries.…”
Section: General Descriptions Of Digital Resilience Of Adolescentssupporting
confidence: 91%
“…Individuals can adapt quickly as they adjust to the digital threats and risks they face based on the situation. Similarly, Ragni et al (16) found that among students with high levels of digital resilience, about 42 percent admitted that they recovered quickly all or most of the time after facing difficulties with digital technology, and another 45 percent of respondents noted that they recovered quickly some of the time. Thus, recovery represents a person bouncing back to their normal activities, just as before the stressful event occurred (11).…”
Section: General Descriptions Of Digital Resilience Of Adolescentsmentioning
confidence: 94%
See 3 more Smart Citations